2020
DOI: 10.1002/jlb.4ma0320-343r
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus directly modulates mouse eosinophil responses

Abstract: Allergic asthma and influenza are common respiratory diseases with a high probability of co‐occurrence. During the 2009 influenza pandemic, hospitalized patients with influenza experienced lower morbidity if asthma was an underlying condition. We have previously demonstrated that acute allergic asthma protects mice from severe influenza and have implicated eosinophils in the airways of mice with allergic asthma as participants in the antiviral response. However, very little is known about how eosinophils respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 132 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…It was observed that increased viral control correlated with higher numbers of eosinophils arriving earlier to the lung during influenza (96). More recent findings show that influenza exposure causes murine eosinophils to up-regulate the expression of genes encoding viral sensors (105), and that these eosinophils can become infected by influenza virus and degranulate in response to influenza (106). Strikingly, adoptive transfer of eosinophils into the airways of A. fumigatus-sensitized mice reduced influenza viral burden and weight loss in response to influenza infection, suggesting these cells are actively beneficial during influenza infection in mice with AAD.…”
Section: Influenza Infection In the Asthmatic Lungmentioning
confidence: 98%
“…It was observed that increased viral control correlated with higher numbers of eosinophils arriving earlier to the lung during influenza (96). More recent findings show that influenza exposure causes murine eosinophils to up-regulate the expression of genes encoding viral sensors (105), and that these eosinophils can become infected by influenza virus and degranulate in response to influenza (106). Strikingly, adoptive transfer of eosinophils into the airways of A. fumigatus-sensitized mice reduced influenza viral burden and weight loss in response to influenza infection, suggesting these cells are actively beneficial during influenza infection in mice with AAD.…”
Section: Influenza Infection In the Asthmatic Lungmentioning
confidence: 98%
“…Likewise, intestinal eosinophils are phenotypically distinguishable from autologous blood eosinophils and express antigen presentation markers not seen on blood eosinophils (46). In addition to type 2 responses, eosinophils exposed to viral (47)(48)(49)(50)(51), bacterial, or fungal pathogens (52)(53)(54) and eosinophils involved in cancer or autoimmunity (reviewed in 9, 55, 56) undergo unique phenotypic changes associated with their ability to differentially regulate activation or suppression of the in ammatory process. Taken together, the emerging evidence indicates that eosinophils are pleiotropic cells, capable of dramatically and dynamically modifying their transcriptomic content in response to microenvironment and in ammatory signals.…”
Section: Technological Difficulties Unique To Eosinophils For Single-cell Transcriptomicsmentioning
confidence: 99%
“…Eosinophils have the capacity to release IL-6 or type 17 mediators that occur in certain patients with exacerbation-prone asthma (144). Moreover, eosinophils have unique functions in viral infections (47)(48)(49)51), when they may produce inducible nitric oxide synthase, take up viral particles, and activate CD8 T cells to kill viruses. In these nuanced disease processes, eosinophils may be contributory cells rather than primary mediators.…”
Section: Eosinophil De Ciency In Mouse Models Of Eosinophilic Diseasementioning
confidence: 99%
“…Several immune cell populations in the lungs have been found to play vital roles in the response to respiratory virus infection (Channappanavar et al, 2016;Dalskov et al, 2020;LeMessurier et al, 2020). We therefore sought to determine if any of the genetic loci identified in our study showed an association with influenza A virus (IAV)-induced disease phenotypes.…”
Section: Relationships Between Baseline Immune Lung Qtl and Respiratory Virus-induced Phenotypesmentioning
confidence: 94%